Research priorities in pediatric rheumatology: The Childhood Arthritis and Rheumatology Research Alliance (CARRA) consensus - Mellins Elizabeth D; O'Neil Kathleen; Schanberg Laura E; Cron Randy Q; Ota Sylvia; Fuhlbrigge Robert C; Feldman Brian M (BMC, 2008)
Abstract Background North American pediatric rheumatologists have created an investigator-initiated research network (the Childhood Arthritis and Rheumatology Research Alliance - CARRA) to facilitate multi-centre studies. One of the first projects undertaken by this network was to define, by consensus, research priorities for the group, and if possible a first group-sponsored clinical trial in which all members could participate. Methods We determined consensus using the Delphi approach. This approach has been used extensively in health research to reach consensus in large groups. It uses several successive iterations of surveys eliciting ideas and opinions from specialists in the field. Three surveys were designed based on this method and were distributed to members of CARRA to elicit and rank-order research priorities. Results A response rate of 87.6% was achieved in the final survey. The most highly ranked research suggestion was to study infliximab treatment of uveitis unresponsive to methotrexate. Other highly ranked suggestions were to study i) the treatment of systemic arthritis with anakinra and ii) the treatment of pediatric systemic lupus erythematosus with mycophenolate mofetil. Conclusion The Delphi approach was an effective and practical method to define research priorities in this group. Ongoing discussion and cooperation among pediatric rheumatologists in CARRA and others world-wide will help in developing further research priorities and to facilitate the execution of clinical trials in the future.